Peranan Pencucian Luka Terhadap Penurunan Kolonisasi Bakteri Pada Luka Kaki Diabetes - Nurbaya Nurbaya; Takdir Tahir; Saldy Yusuf (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
ABSTRACT Background: Diabetic ulcer is a major complication of diabetes and is the main cause of infection. One of the efforts or interventions to reduce infection by doing wound cleansing, but research on the effects of wound cleansing on bacterial colonization is still limited. The purpose of this literature study was to determine the effectiveness of using a type of wound cleansing on changes in bacterial colonization in DM wounds. Methods: The data base used in making this review literature is Pubmed, Science Direct, Google Scholar and Cochrane. there are 144 articles identified and published from 2010-2018. Of the 144 articles 8 articles that met the inclusion criteria. Results: Various wound cleansing solutions are used to optimize the wound healing process and the effect is quite good in decreasing bacterial colonies in DM wounds. Conclusion: wound cleansing type ESWA has a bactericidal effect, is effective in reducing bacterial colonization, and economically it is expected to be a concern in the treatment process injury, research is needed as to whether ESWA washing types can be used to reduce bacterial colonization in DM wounds.